Tingkat Keberhasilan Implementasi Enterprise Resources Planning di BUMN Sektor Manufaktur di Indonesia - Simamora, Bachtiar H.; Wicaksono, Kuspuji C.B.; Toindo, Harly; Rudi, Rudi (Bina Nusantara University, 2015)
Implementation of the Enterprise Resource Planning (ERP) is an investment that does not appear in an organization. Indonesia State-Owned Enterprise, in particular manufacturing sector that have the leeway and autonomy to do ERP investments in supporting the achievement of its vision and mission. The World Economic Forum, put Indonesia on a ranking of 82 among the countries in the world in ICT utilization. This research aimed to test how big the investment that has been implanted in the area of information technology in the manufacturing sector, State-Owned Enterprises and the extent of the investment for the competitiveness of the company as well as its contribution to the wind of change on the manufactures business in Indonesia. This research was conducted to explore the performance of ERP implementation project. ERP implementation success rates seen from aspect of project management, determination of critical elements of urgency and contextual factors. The result is that all independent variables influence significantly to the success of the implementation of ERP of SOEâs manufactures. The greatest contribution to the success of such in sequence is an element of urgency determination of critical factors, a contextual factors, and management of the project.